Concepts in ski jumping biomechanics and potential transfer to other sports - Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The specificity of ski jumping requires particular considerations and methodologies regarding the biomechanical context. In this paper some of these issues are presented and discussed. Furthermore, potential transfer of these concepts and methodologies to other sports will be presented. The topics cover aspects of conceptual considerations regarding experimental research, lab and field measurements, ski jumping specific methodologies, imitation exercises and the relevance of biomechanics research within the complex research network. Starting from ski jumping the conceptual issues are discussed for demonstrating the potential transfer to other sports and optional applications in order to provide scientifically based enhancement of performance, effect of training concepts, comfort and injury prevention.